Reinternações psiquiátricas : análise das características sociodemográficas, clínicas e do uso da rede de atenção psicossocial de usuários com transtornos mentais - Zanardo, Gabriela Lemos de Pinho (2016)
In this study, we aim to analyze psychiatric readmissions regarding sociodemographic, clinic, and use of Network for Psychosocial Care data of individuals with mental disorders. We carried out two studies; the first is a critical literature review using systematic review as method, in order to analyze papers published in the last five years having “psychiatric readmission” as the main topic. We intended to get familiar with the criteria used to define what psychiatric readmission is, and to analyze associated factors. From the research on PubMed, BVS, PsycInfo databases, we selected 26 papers. Literature analysis shows the existence of various frequent readmission criteria, and, thus, different described prevalence. The associations among these readmissions with sociodemographic and clinic variables, and network psychosocial care data showed contradictory results at times, which might be associated to the studies methodological differences. The second study is empirical, with a cross-sectional design, and a sample of 96 inpatients in a hospital of Porto Alegre. We aimed to investigate sociodemographic, clinic, and follow-up characteristics in a health service associated to psychiatric admissions and readmissions. The dependent variables were first admission, and frequent readmissions. More than half of the sample (53.1%) were female, 51% were single, and the average age was 44.3 years old. From clinic data, 37.5% (n=36) of the users were in their first admission, and 36% (n=35) met the criteria for frequent readmission. Users with frequent readmissions significantly mentioned fewer people on whom they could rely, and lived with a significant smaller number of people than the rest of the sample. Alternatively, users in first readmission had, with less frequency, bond with health services other than hospitals, using hospitals as an entrance door to mental health care. We highlight the importance of the findings on Network for Psychosocial Care follow-up, as 34.4% of the sample did not have follow-up before admission, and only 4.1% used services of psychosocial rehabilitation. These admissions might have been avoided if users had had bonds with health services, especially with primary care, which could detect mental health care needs, and offer care before the need of admission. Therefore, hospitals have a central and strategical role as network articulator to perform the connection with Network for Psychosocial Care services, even if this does not guarantee access to services. We emphasize that the ones who have fewer people on whom they can rely, and consequently less social support, have higher probability of having more psychiatric readmissions. Although results indicate some clues about factors associated with frequent readmissions, we highlight the importance of stablishing an agreement on frequent readmission criterion, as well as developing more studies on the theme, both nationally and internationally, in order to increase the comprehension on this phenomenon.